Maternal Work Status and Nutritional Knowledge as Predictors of Toddler Stunting: Evidence from Asahan Regency, Indonesia - Mestika Rija Helti; Nila Hayati (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Stunting remains a significant public health concern in Indonesia, particularly in rural and semi-urban areas where maternal knowledge and employment status intersect with child-rearing practices. This study investigates the relationship between maternal employment, maternal knowledge, and the incidence of stunting among toddlers in the catchment area of the Simpang Empat Primary Healthcare Center, Asahan Regency. A quantitative, cross-sectional design was utilized, with data collected from 57 mothers of children aged 12-59 months via structured questionnaires distributed through Google Forms. Key variables included maternal employment status, maternal knowledge of child growth and nutrition, and child nutritional status measured by height-for-age Z-scores (HAZ), in accordance with the WHO Child Growth Standards (2006). Descriptive analysis revealed that 52.6% of mothers were unemployed, and 54.4% exhibited limited knowledge of early childhood development and nutrition. The prevalence of stunting in the sample was 43.8%. Bivariate analysis using the chi-square test identified statistically significant associations between stunting and both maternal employment status (p = 0.000) and maternal knowledge (p = 0.003). Notably, stunting was more prevalent among children whose mothers had poor nutritional knowledge, regardless of employment status. These findings underscore the dual influence of socioeconomic and cognitive factors on child nutritional outcomes. Maternal employment alone does not mitigate the risk of stunting unless accompanied by sufficient nutritional literacy and caregiving capacity. The study highlights the urgent need for community-based health education initiatives through primary healthcare centers and cadres, supported by flexible and inclusive maternal support programs that address time constraints and knowledge gaps. Strengthening maternal knowledge across socioeconomic strata is critical to achieving Indonesia's national stunting reduction targets and advancing global child development goals Keywords: Stunting, Maternal Work Status, Maternal Knowledge, Toddler Nutrition